An Ethnography of a Mamelodi West Hostel : analysing how Stigma, Gender, Crime and Political Structure is understood outside and within the hostel - McNeill, Fraser G. (University of Pretoria, 2019)
Dissertation (MSocSci Anthropology)--University of Pretoria, 2018.